99mTc-Leukocyte Scintigraphy in Prosthetic Vascular Graft Infections - Vorne, M.; Laitinen, J.; Lehtonen, J.; Soini, I.; Toivio, I.; Mokka, R. (Nuklearmedizin - NuclearMedicine, 1989)
The aim of this study was to determine the diagnostic value of scintigraphy with 99mTc-HMPAO-labelled leukocytes for the detection of prosthetic vascular graft infection. 51 scans were recorded in 19 patients with suspected vascular graft infection and 8 control patients. Three-phase scanning was used at 0.5, 3 – 6 and 18–24 h. 13 vascular graft infections (10 early, 3 late) were found. 12 of these healed with antibiotics and only one patient with late infection had to be reoperated. None of them died during the follow-up period. The sensitivity was 100% and the specificity 96%. 99mTc-leukocyte scintigraphy seems a useful tool to detect vascular graft infection and to differentiate it from infections elsewhere. The results suggest that the incidence of vascular graft infection may be greater, and the mortality rate lower, than supposed before.Die diagnostische Brauchbarkeit der Szintigraphie mit 99mTc-HMPAOmarkierten Leukozyten zum Nachweis infizierter Gefäßprothesen wurde bewertet. Untersucht wurden 19 Patienten mit Verdacht auf Infektion in der Gefäßprothese und 8 Kontrollpatienten (insgesamt 51 Leukozytenszintigramme). Die Szintigraphie wurde in drei zeitlichen Perioden (0.5, 3 – 6 und 18–24 h p.i.) durchgeführt. 13 Infektionen der Gefäßprothese (10 frühe, drei späte) wurden entdeckt. 12 davon konnten mit Antibiotika ausgeheilt werden. Nur ein Patient mit einer Infektion im späten Stadium mußte nochmals operiert werden. Die Sensitivität betrug 100%, die Spezifität 96%. Die 99mTc-HMPAO-Leukozytenszintigraphie erwies sich als brauchbare Methode, um Infektionen bei Gefäßprothesen zu erfassen und sie von Infektionen anderenorts abzugrenzen. Die Ergebnisse zeigen, daß die Häufigkeit der Infektion einer Gefäßprothese größer und die Mortalität kleiner sein dürfte als bisher angenommen.